Utilization and perceptions of language assistance services by medical trainees: a pathway to language certification - Tucker Avra; Daniel Cordova; Breena Taira; Jesus R. Torres (AIMS Press, 2024)
Background Access to language assistance is a patient's right under federal law. Despite this, underuse of language services persists. Objective The aim of this study was to explore the interest in obtaining bilingual certification and to describe perspectives on language services by resident physicians. Methods Between May and August 2021, we conducted a cross-sectional survey of residents at a public, urban hospital serving mostly patients with limited English proficiency (LEP). We assessed resident perspectives on language services, exposure to language-related trainings, non-English language (NEL) skills, and interest in bilingual certification. Results A total of 214 residents of 289 completed the survey (a 74% response rate). Of the 95 residents who used their NEL for patient care, 65 (68%) would be interested in bilingual certification. Sixty-nine (33%), 65 (31%), and 95 (45%) residents disagreed or strongly disagreed with being satisfied with the language services available, convenience, and sufficient equipment, respectively. Furthermore, 28 (13%) disagreed or strongly disagreed that they could achieve bi-directional communication with LEP patients. Conclusions Over a quarter of the residents expressed interest in bilingual certification and were likely to pass the certification exam. Many reported using their own NEL skills without certification and held negative views on services and trainings.